Sosialisasi Literasi Keuangan Syariah Sebagai Upaya Peningkatan Pemahaman Ekonomi Masyarakat Desa Tamiang - Amru Hasibuan; Akhir Saleh Pulungan; Ismail Nasution; Kali Junjung Hasibuan; Gelar Praminan Pasaribu; Laila Suriati Harahap; Nur Kasima Pasaribu; Riswan Santoso (Jurnal Transformasi Pendidikan Indonesia, 2025)
The community's low level of understanding of financial literacy, particularly Islamic finance, is one of the factors inhibiting economic growth at the rural level. This situation also occurs in Tamiang Village, Batang Lubu Sutam District, Padang Lawas Regency, where the majority of residents still manage their finances traditionally without considering Islamic principles or appropriate management strategies. This problem impacts the community's limitations in developing businesses, managing income, and accessing Islamic financial services. To address this issue, a Community Service Program in the form of "Islamic Financial Literacy Socialization" was conducted, focusing on educating and assisting the community in managing finances according to Islamic principles. The objective of this activity was to increase the community's understanding and skills in managing household and small business finances, thereby boosting family economic growth. Implementation methods included interactive lectures, group discussions, financial management simulations, and direct consultations, with a strategy involving community leaders, MSMEs, and village officials. The results of the activity showed an increase in community understanding of the basic concepts of Islamic finance, the importance of financial planning, and the utilization of Islamic financial products.  As a result, people are becoming more aware of the importance of saving, avoiding usurious practices, and becoming wiser in managing their income and expenses, thus contributing to improved family well-being.